1997
DOI: 10.1128/jb.179.21.6749-6755.1997
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of anaerobic fermentative growth of Bacillus subtilis: identification of fermentation end products and genes required for growth

Abstract: Bacillus subtilis can grow anaerobically by respiration with nitrate as a terminal electron acceptor. In the absence of external electron acceptors, it grows by fermentation. Identification of fermentation products by using in vivo nuclear magnetic resonance scans of whole cultures indicated that B. subtilis grows by mixed acid-butanediol fermentation but that no formate is produced. An ace mutant that lacks pyruvate dehydrogenase (PDH) activity was unable to grow anaerobically and produced hardly any fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
155
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(164 citation statements)
references
References 38 publications
6
155
0
3
Order By: Relevance
“…It was concluded that pyruvate might serve as a stimulating agent that triggers expression of genes required for mixed acid fermentation, as the intracellular pyruvate pool might be too small to initiate expression of genes required for fermentation. Also, pyruvate was discussed as a precursor of certain amino acids that cannot be synthesized by B. subtilis [19]. Similar conclusions were drawn before from observations made with the methanogenic archaeon Methanosarcina barkeri [17].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…It was concluded that pyruvate might serve as a stimulating agent that triggers expression of genes required for mixed acid fermentation, as the intracellular pyruvate pool might be too small to initiate expression of genes required for fermentation. Also, pyruvate was discussed as a precursor of certain amino acids that cannot be synthesized by B. subtilis [19]. Similar conclusions were drawn before from observations made with the methanogenic archaeon Methanosarcina barkeri [17].…”
Section: Discussionsupporting
confidence: 58%
“…Limited growth was possible also if no supplements but only glucose and pyruvate were added. Also Bacillus subtilis can grow by fermentation of glucose in anoxic, non-reduced Spizizen's medium amended with amino acid mixtures, however, addition of pyruvate to cultures with glucose augmented growth significantly [19]. It was concluded that pyruvate might serve as a stimulating agent that triggers expression of genes required for mixed acid fermentation, as the intracellular pyruvate pool might be too small to initiate expression of genes required for fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For experiments with B. pseudomallei, Burkholderia thailandensis, or Pseudomonas aeruginosa, cultures were grown in M9 medium (17) that contained glucose (0.2%) and thiamine (0.5 g/ml). For experiments with Bacillus subtilis, cultures were grown in Spizizen's minimal medium (18) containing glucose (1%) and tryptophan (50 g/ml) along with glutamate (2 mg/ml), KNO 3 (0.2%), and trace elements as described by Nakano et al (19). The MIC values reported for each strain are the median values from three to six independent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of nitrate, it undergoes fermentation to generate ATP through glycolysis. Anaerobic fermentation of B. subtilis requires glucose and pyruvate (13). In the experiments described here, we filled tubes with aliquots of a cell suspension (starting optical density at 600 nm [OD 600 ] of 0.02).…”
mentioning
confidence: 99%